Cardiac Rehabilitation practitioners’ views on patients’ psychological needs: a qualitative study - Wray, Laura; Capobianco, Lora; Wells, Adrian (Frontiers in Psychiatry, 2024)
Background Psychological difficulties are prevalent in patients undergoing Cardiac Rehabilitation (CR). Recent guidelines recommend that practitioners inquire and address patients’ psychological concerns during CR. Therefore, Study One aimed to explore practitioners’ understanding of patients’ psychological needs, their confidence in supporting those needs, and their views on whether current CR meets patients’ needs. Study Two aimed to validate Study Ones’ findings among a wider sample of CR practitioners. Methods This study consisted of two interrelated qualitative interviews. Study One utilised qualitative interview data from the PATHWAY trial (REC Reference:15/NW/0163), while Study Two utilised new interview data collected as part of the PATHWAY Beacons study (REC Reference: 22/HRA/2220). In Study One semi-structured interviews with six CR practitioners were analysed using thematic analysis. In Study Two, 11 CR practitioners across England were interviewed using member-checking principles. Transcripts were coded systematically using the codes developed in Study One and, through constant comparative analysis. Results Four main themes were identified: staff’s awareness of mental health problems, CR patients’ needs, staff’s self-efficacy to support patients’ psychological needs, and current psychological provision in CR. The main themes and 11 subthemes were transferable to a wider range of CR practitioners, thereby indicating the trustworthiness of the findings. Conclusion Practitioners described that patients experience a range of psychological concerns, including adjustment difficulties, anxiety, and cardiac and noncardiac worries. Most practitioners normalise patient concerns and offer relaxation techniques. However, practitioners have noted that patients often have complex psychological needs, but practitioners’ confidence in discussing and supporting psychological concerns varies. Practitioners expressed the need for training to support patients’ psychological needs.